Assessing The Role Of The Police In Dealing With Criminal Acts Of Theft Committed By Minors - Nur'ain Lihawa (Estudiante Law Journal, 2019)
In essence, children cannot protect themselves from various actions that cause mental, physical, social, losses in various areas of life. For children who commit criminal acts, not all can be applied Diversi and Based on the description above, factors that inhibit the police in tackling the crime of theft committed by minors are: lack of understanding of the community related to Diversi, in the judicial process, is the understanding of the community about the child who committed the crime, and the lack of understanding of state responsibility towards children,  Underprivileged children such as abandoned children, victims do not know the identity of the perpetrator, there are no witnesses.